2021
DOI: 10.1039/d1ea00032b
|View full text |Cite
|
Sign up to set email alerts
|

Condensation sink of atmospheric vapors: the effect of vapor properties and the resulting uncertainties

Abstract: Aerosol particles affect the climate and human health. Thus, understanding and accurately quantifying the processes associated with secondary formation of aerosol particles is highly important. The loss rate of vapor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The other sink for sulfuric acid dimer is coagulation with larger particles (the CS). During the measurements, the CS for sulfuric acid monomer varied between 0.01 and 0.25 s −1 , but the CS for the dimers is anticipated to be slower than the monomer by nearly a half due to the larger cluster size and mass than the sulfuric acid monomer (Tuovinen et al., 2021). Evaporation is the dominant sink for dimers during clean periods (CS < 0.05 s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The other sink for sulfuric acid dimer is coagulation with larger particles (the CS). During the measurements, the CS for sulfuric acid monomer varied between 0.01 and 0.25 s −1 , but the CS for the dimers is anticipated to be slower than the monomer by nearly a half due to the larger cluster size and mass than the sulfuric acid monomer (Tuovinen et al., 2021). Evaporation is the dominant sink for dimers during clean periods (CS < 0.05 s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is possible that only a fraction of all the collisions lead to coagulation due to e.g., chemical properties of the particles. This is analogous to effectiveness of CS in removing condensable vapors such as sulfuric acid (Tuovinen et al, 2021(Tuovinen et al, , 2020, which has been shown to be higher for ammonium-nitrate rich background particles (Du et al, 2022). If the effectiveness of CoagS for particles between 1.5 nm and 3 nm varies between 0.25 and 1.0, almost all the observed J3/J1.5 that are larger than predicted based on the simulations or L-2007 can be explained.…”
Section: Effect Of Uncertainties and Assumptions On Survival Probabil...mentioning
confidence: 68%
“…This phenomenon was attributed to oligomer and/or organosulfate formation. Couvidat et al (2018) and Tuovinen et al (2021) finally stated that BiA0D compounds are not able to condensate according to the kelvin effect but few of them, with low saturation vapor pressure, contribute to the growth of particle per condensation. This present work proposes to keep the same aerosol formation mechanism as proposed in outdoor air quality model for BiA0D, but creating a new surrogate BiA0D' with a low saturation vapor pressure (see Section 2.2.3).…”
Section: Nucleationmentioning
confidence: 99%